IMPLEMENTASI KEBIJAKAN PENGELOLAAN PENGURUS KELOMPOK BELAJAR SKEMA BARU DI UNIVERSITAS TERBUKA - Dwi Kristanti (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2018)
The learning system at the Open University, both abroad and in Indonesia, there is a learning program that really demands student independence. This study aims to analyze the implementation of management policies of the management of the new scheme of study groups at the Open University of UPBJJ-UT Bengkulu and UPBJJ-UT Padang. The number of respondents in this study were 445 Bengkulu students and in Padang. The research data analysis used was the independent sample t-test. The collected data was analyzed using Statistical Package for Social Sciences (SPSS) software version 16.0 for Windows. The results of the first study, show that obtained F-count value 42,808 and sig value. 0,000 < 0,005. Second, the implementation of management policies has a t-count value of 6.872 and a sig value. 0,000 < 0,005. And finally, the implementation of management policies has a t-count value of 7.404 and a sig value. 0,000 < 0,005. Based on the results of the study indicate that the two regions still need supervision of the performance of the study group administrators at the Open University. Student satisfaction is considered to be lacking in POKJAR's performance. But in the category often and very often the UT Padang region is bigger than the UT Bengkulu region, this also shows that the oversight is still more than the Bengkulu Open University entity in carrying out its duties and authority as the management of the study group so that service to students is not constrained and students understand Open University procedures.